Exploring Multi-dimensional Paths to Enhancing University Education Quality in the New Era (Journal of humanities and social sciences exploratio, 2026)
In the era of deepening implementation of the Education-Powerhouse Strategy, enhancing the quality of university education has become a core issue of higher education reform. This paper identifies eight dimensions—concept innovation, curriculum and teaching quality improvement, campus culture shaping, interdisciplinary education practice, curriculum system optimization, teacher ethics cultivation, integration of traditional culture into modern teaching, and student agency—and analyzes their implementation logic and practical approaches with vivid university case studies. It explores a multi-dimensional, synergistic model for improving education quality, offering theoretical insights and practical references for cultivating high-caliber talents.
Keywords: University education quality; Educational philosophy; Interdisciplinary education; Curriculum system; Student agency; Teacher ethics; Traditional culture